Produktivitas usaha budidaya rumput laut Kappaphycus alvarezii di Kelurahan Bandar Batauga Kabupaten Buton Selatan Sulawesi Tenggara - Kiran; Riani, Irdam; Annaastasia, Nurhuda; Siang, Roslindah Daeng; Sidiq, Azwar (Universitas Halu Oleo, 2024)
This research aims to determine capital productivity and seed productivity in seaweed cultivation businesses. This research was conducted in Bandar Batauga Village, Batauga District, South Buton Regency in February 2023. The respondents in this research were 10 seaweed cultivators using the census method. Data collection techniques were obtained through observation, interviews, documentation and literature study. Data analysis uses quantitative analysis, using the formula for costs, revenues, profits, and productivity. The results of the research show that the average total costs and average revenues from seaweed cultivation are Rp10,701,293/cycle and Rp58,280,000/cycle respectively. The average profit is Rp47,578,707/cycle. The average productivity of capital obtained by seaweed cultivation is 5.33, which means that every Rp1 of capital will generate revenue of Rp5.33. The average productivity of wet seeds into wet seaweed is 7.78 and into dry seaweed is 1.11. This means that the productivity of seeds can be concluded that every 1 kg of wet seeds will produce 7.78 kg of wet seaweed and 1.11 kg of dry seaweed.